2001
DOI: 10.1046/j.1365-2885.2001.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ricobendazole in calves

Abstract: The pharmacokinetics of ricobendazole (RBZ) and its major metabolite albendazole sulphone (ABZSO2) were studied in six calves, after administration of RBZ (7.5 mg/kg), using a 10% experimental solution by the intravenous (i.v.) route, a 10% commercial solution by the subcutaneous (s.c.) route, and a 10% experimental suspension by the intraruminal (i.r.) route. Blood samples were drawn during a 60-h period. Plasma drug and metabolite concentrations were determined by HPLC. The pharmacokinetic evaluation in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 14 publications
2
31
0
1
Order By: Relevance
“…[3][4][5][6] The injection is formulated as a highly acidic solution with additional solubilization by organic co-solvents. 5 Reports have indicated that it is effective as an anthelmintic agent 8,[20][21][22] but causes injection site reactions, 5 so alternative better tolerated formulations are sought. The dosage administered in efficacy and pharmacokinetic studies varied from 3.75 6 to 7.5 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[3][4][5][6] The injection is formulated as a highly acidic solution with additional solubilization by organic co-solvents. 5 Reports have indicated that it is effective as an anthelmintic agent 8,[20][21][22] but causes injection site reactions, 5 so alternative better tolerated formulations are sought. The dosage administered in efficacy and pharmacokinetic studies varied from 3.75 6 to 7.5 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…The mixtures were then centrifuged at 3000 rpm for 10 min and the aqueous layer taken for analysis by HPLC. Experiments were repeated five times and apparent partition coefficients (P) were calculated using Equation 5.…”
Section: Apparent Partition Coefficient Of Rbzmentioning
confidence: 99%
See 2 more Smart Citations
“…Albendazole [ABZ] is an inactive moiety but it readily gets metabolized to an active metabolite Albendazole sulfoxide [ABZSO] then this ABZSO is then further metabolized to an inactive metabolite Albendazole sulfone [ABZSO2] [10]. As ABZ is metabolized extensively, therefore, the plasma concentration of ABZ is also very low as a result the pharmacokinetic studies were been done using Albendazole sulfoxide [ABZSO] as an active metabolite and Albendazole sulfone [ABZSO2] as an inactive metabolite [11][12][13][14][15]. Metabolism of Praziquantel [PRQ] occurs giving a number of hydroxylated metabolites [16][17][18], among which the active metabolite is mainly trans-4-hydroxypraziquantel [TRANS], an active metabolite [19].…”
mentioning
confidence: 99%